A80 ADHERENCE TO GUIDELINES AND BEST PRACTICES FOR IBD FLARE MANAGEMENT AND CORTICOSTEROID ADMINISTRATION: A RETROSPECTIVE CHART REVIEW. (15th March 2019) - Sutton, R T; Lytvyak, E; Pincock, D; Baumgart, D C; Sadowski, D; Fedorak, R; Kroeker, K
Abstract: Background: Induction and maintenance of remission is a primary treatment goal for inflammatory bowel disease (IBD). Active disease is often treated with corticosteroids (CS). Although effective, CS have significant negative effects, and not recommended for long term or frequent use, especially when safer medications are now available. Nonetheless, literature suggests that cumulative exposure to CS in IBD patients has not changed. Gaps in clinician adherence to international guidelines for IBD care have also been identified. Aims: We aim to: (1) assess adherence of practitioners to guidelines for CS use and treatment of disease flares, and (2) associate guideline adherence with outcomes at 12 months. Methods: A retrospective, single-center study using data collected from outpatients of the University of Alberta IBD Clinic, receiving > 1 dispensation of CS from an IBD practitioner between March 2014–2016. Data for CS dispensations including and for 18 months following the initial dispensation were extracted from provincial databases. Other data was manually extracted from the region-specific electronic medical record (EMR). Regression analyses were performed with clinical remission as the dependent variable (95% confidence). Results: Of 345 charts identified, 244 met inclusion. The majority, 157 (64.3%), had Crohn's disease (CD). At the initial dispensation, median age was 40 (IQR: 28–50) years. Maintenance medications: 72 (29.5%) on no IBD medication, 75 (30.7%) 5-ASA only, 34 (13.9%) immunomodulators, and 63 (25.8%) biologic therapy. CS were prescribed in clinic for 125 (51.2%), at endoscopy for 54 (22.1%), in hospital for 29 (11.9%), and by telephone for 36 (14.8%). The majority of CS prescribed were prednisone (176, 72.1%), the remainder budesonide. Conclusions: There are gaps between guidelines and clinical practice for some aspects of IBD patient care, particularly documentation and fecal calprotectin. Providers seem more likely to document clinical scores when patients have severe disease. Making better use of EMR functionality may be of utility to automate and improve clinical documentation and testing. Additionally, prescribing of steroids beyond an initial flare does not appear to be associated with better outcome. Funding Agencies: CCC, CIHRUniversity of Alberta